PENANGANAN PELAYANAN PENGADUAN PELANGGANMENGENAI KELUHAN TIDAK DAPAT AIR (TDA) DI PDAM SURYA SEMBADA SURABAYA - Imaroh, Hafidlotul Ilmi (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Handling of Customer Service Complaints about Unconditional Comlaints (TDA) in Surya House Sembada Surabaya. OneÂ formÂ ofÂ aÂ qualityÂ publicÂ serviceÂ isÂ toÂ giveÂ freedomÂ toÂ theÂ communityÂ inÂ presenting complaints and complaint. Complaints this can be approached in various ways that is either directly or through social media. But variety of ways the complaint is unsatisfactory society for related parties in response to a customer complaint not well responded. Where people are complain about the about cannot water, While the water has an important role as a basic requirement in daily necessities. Hence the researchers interested in do research by the title â€œHandlingÂ CustomerÂ ServiceÂ ComplaintsÂ aboutÂ ComplaintsÂ Canâ€™tÂ WaterÂ (TDA)Â inÂ PDAM Surya Sembada Surabayaâ€. The purpose of this research is to find how handling customer service complaints about complaints cannot water (TDA). The methods used in this research is qualitative research methods with the descriptive approach. Based on the results of the study it can be concluded that the proper handling of customer complaints services basically has been carried out in accordance with standard operational procedures and in accordance with the standard of service from Kepmenpan No. 63 in 2003 but some the peoples complaint about the service providers less patient in providing services to customers And in the service it has not satisfy as the water is still muddy and unfit to be consumed. Â Keywords: Service, Customer Complaints, Complaints